Theoretical and experimental investigation of the plasma source with argon RF barrier discharge at atmospheric pressure - Bazhenov, V.Yu.; Tsiolko, V.V.; Piun, V.M.; Chaplinskiy, R.Yu.; Kuzmichev, A.I. (Вопросы атомной науки и техники, 2014)
Glow characteristics of capacitive radio frequency discharge with isolated electrodes in atmospheric pressure argon in low-current α and high-current γ modes are determined experimentally and calculated by the hybrid hydro-dynamic model. Comparative analysis of obtained experimental data and simulated spatio-temporal distributions of concentrations of discharge plasma electrons and heavy species, mean energy of electrons in the RF barrier discharge enabled interpretation of the discharge structure peculiarities in low-current α, α-γ transition and high-current γ modes. Характеристики емкостного высокочастотного разряда с изолированными электродами в аргоне атмосферного давления в слаботочном α- и сильноточном γ-режимах установлены експериментально и рассчитаны с помощью гибридной гидродинамической модели. Сравнительный анализ полученных экспериментальных данных и смоделированных пространственно-временных распределений концентраций электронов и тяжелых частиц, средней энергии электронов в ВЧ-барьерном разряде дал возможность интерпретировать особенности структуры разряда в слаботочном α, переходном α-γ и сильноточном γ-режимах разряда. Характеристики ємнісного високочастотного розряду з ізольованими електродами в аргоні атмосферного тиску в слабкострумовому α- та сильнострумовому γ-режимах встановлено експериментально та розраховано за допомогою гібридної гідродинамічної моделі. Порівняльний аналіз одержаних експериментальних даних та змодельованих просторово-часових розподілів густин електронів та важких часток, середньої енергії електронів у ВЧ-бар’єрному розряді дав можливість інтерпретувати особливості структури розряду в слабкострумовому α, перехідному α-γ та сильнострумовому γ-режимах розряду.